Home, clinic, and ambulatory blood pressure monitoring in children with chronic renal failure - Wühl, Elke; Hadtstein, Charlotte; Mehls, Otto; Schaefer, Franz (Pediatric research, 2004)
Ambulatory blood pressure monitoring (ABPM) provides superior information for diagnosis and treatment of pediatric hypertension, but for reasons of practicality, clinic blood pressure measurements (CBP) are still the primary diagnostic tool. Regular home blood pressure measurements (HBP) may be an alternative to ABPM, but this technique awaits validation in practice. We analyzed the concordance of ABPM, CBP and HBP in 118 pediatric patients (3-19 y) with chronic renal failure. HBP readings (10.5 ± 5.4 per patient) were averaged for one week around the day of ABPM and CBP. Mean arterial pressure (MAP) measured by HBP (84.0 ± 10 mm Hg) was significantly lower than both CBP (86.1 ± 14.1 mm Hg, P < 0.05) and daytime ABPM (90.3 ± 10.4 mm Hg, P < 0.05). HBP detected hypertensive patients with greater specificity (82 versus 70%), but lower sensitivity (52 versus 70%) than CBP. The fraction of patients rated erroneously hypertensive was 23% with CBP, but only 14% with HBP. The 95% limits of agreement with ABPM were narrower for HBP (-23 to10 mm Hg) than for CBP (-30 to 21 mm Hg). CBP, but not HBP measurements, were less precise in the upper BP range. The accuracy of HBP measurements did not change with use over a six months time period. In conclusion, HBP was superior to CBP in predicting ABPM, but neither CBP nor HBP detected hypertension with enough sensitivity or specificity to replace ABPM. The greater specificity of HBP compared with CBP makes it a more suitable tool for diagnosis, rather than screening, of hypertension in children.
Members of the ESCAPE (Effect of Strict Blood Pressure Control and ACE Inhibition on the Progression of CRF in Pediatric Patients) Trial Group: A. Anarat, A. Bakkaloglu, A. Peco-Antic, U. Querfeld, J. Gellermann, P. Sallay, D. Drozdz, K.-E. Bonzel, A.-M. Wingen, A. Zurowska, F. Perfumo, A. Canepa, D.E. Müller-Wiefel, K. Zepf, G. Offner, B. Enke, O. Mehls, F. Schaefer, E. Wühl, C. Hadtstein, U. Berg, G. Celsi, S. Emre, A. Sirin, I. Bilge, S. Çaliskan, S. Mir, E. Serdaroglu, C. Greiner, H. Eichstädt, K. Hohbach-Hohenfellner, N. Jeck, A. Appiani, G. Ardissino, S. Testa, G. Montini, P. Niaudet, M. Charbit, J. Dusek, A. Caldas-Afonso, S. Picca, C. Matteucci, M. Wigger, M. Fischbach, J. Terzic, J. Fydryk, T. Urasinski, R. Coppo, L. Peruzzi, A. Jankauskiene, M. Litwin, M. Abuauba, R. Grenda, K. Arbeiter, T.J. Neuhaus
Gesehen am 22.01.2021